Analisis Respon Siswa Terhadap Merdeka Belajar Berbasis Teknologi Informasi Pasca Pandemi Covid 19 - Rusdiah, Rusdiah (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2022)
Keywords: Information technology provides various learning resources to make it easier for students to study independently, anytime, and anywhere. This is in line with the Merdeka Learning curriculum program that is being run by the government. The purpose of this study was to determine student responses to the Information Technology-based Learning Freedom curriculum. The research method used was quantitative descriptive research by collecting data through a questionnaire given to 80 students of class XI SMA in Banjar Regency. The results of the study found that 100% of the digital technology used by students was social media in the form of Whatsapp and 72.09% Google Meet to communicate with teachers. Then to find information,100% used  Google,  33.80% used  the Teacher's  Room,  65.97% used Brainly,  56.64% used Wikipedia, and 62.35% used YouTube. 36.30% used Quizizz and 43.75% used the Duolingo application to get practice questions. While students who find it easy to understand material through communication media as much as 94.87% and 5.12% find it difficult.